Pendidikan Karakter di Sekolah Dasar melalui Implementasi Kurikulum Merdeka - Rahayu, Nina; Triani, Rina; Arif, Muhammad; Wulandari, Febriyantika (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2025)
Character education is essential to produce a generation of individuals with good morals. Merdeka Curriculum, a new approach to teaching in primary schools, can help better integrate character values into the education process. This research aims to analyse how character education can be implemented in primary schools using Merdeka Curriculum. This research technique is library research, which refers to various publications as relevant research related to character education and Merdeka Curriculum. The findings of the analysis show that Merdeka Curriculum offers a more adaptive and contextualised teaching approach that encourages students to develop their character through project-based learning activities such as the Pancasila Student Profile Strengthening Project (P5). The research also identified challenges and strategies in integrating character values into school learning. Cooperation between educators, parents and the community can be a support to ensure sustainability in the application of character values in students' lives. Keywords: Character Education, Pancasila Learner Profile Amplifier, and Independent Curriculum